Business strategies of the Minsa Group - Cortés-Castellanos, Uriel R. (2023)
In Mexico, in the food industry there are thousands of economic units that guarantee internal demand, however, the market is controlled by large companies. The production of corn flour does not escape this reality, since two large participants are identified: Gruma and Minsa. Objective: to analyze the business strategies used by Grupo Minsa to consolidate one of the most important economic groups in the food sector in Mexico. Methods: the methods used were descriptive, as well as historical-analytical; Likewise, primary and secondary sources were consulted, such as Grupo Minsa's annual reports sent to the Mexican Stock Exchange (BMV), scientific articles, books and the company's website. Results: among the strategies used by the company, the following stand out: investments, mergers, acquisitions, divestments and differentiation strategies. Conclusions: Grupo Minsa transitioned from a state company to a private one in the nineties and thanks to the State subsidy it maintained levels of accumulation that allowed it to strengthen its production plant and guarantee its permanence in the market.